Perlindungan Hukum Para Pihak dalam Perjanjian Jual Beli Melalui Media Elektronik - Pande Bagus Yoga Pratama Putra; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Warmadewa Press, 2021)
Electronic commerce (E-commerce is basically an act in which contact online transactions using the internet media, and also the existence of E-Commerce is a promising business alternative to be implemented today. This study aims to analyze the validity of the sale-purchase agreement through the media. electronic or internet according to Law No. 11 of 2008 and knowing the form of legal protection for parties in sale and purchase agreements through electronic media in the event of a failure. The research method used is normative legal research with a bullying approach. wan achievement, the party who is responsible for all legal consequences in the implementation of electronic transactions is if it is done alone, all legal consequences in the execution of the transaction are the responsibility of the transacting parties if it is done by granting power of attorney all legal consequences in the implementation of t Electronic transactions are the responsibility of the attorney if done through an electronic agent. All legal consequences in the implementation of electronic transactions are the responsibility of the electronic agent operators. It's simple if in this case an honest character is needed in good faith, where the seller and the buyer must be honest with each other, there are no parties and are harmed for their benefit only so that a valid agreement occurs, and also the goods being traded do not violate the law in Indonesia, such as sharp weapons, protected animals, human trafficking, and drugs.